Uma investiga????o sobre os tipos de confian??a e seu desenvolvimento em neg??cios ???business to business??? - Santos, Claudia Cincotto dos (2007)
Trust has been considered very important in relationships among business-to-business transactions channels. When present, it supports long-term relations, reduces risks and encourages larger investments between the parties involved. It is also a concept, which is extremely complex, that changes its facet according to the evolution of each situation. Understanding the complexity of this issue, as well as its development is mandatory in order to define the marketing strategies to be adopted for each customer segment. This dissertation tries to identify how trust is developed in different relationships among organizations, verifying the evolution with the intensity of its distinct types that an organization might have regarding to its supplier. To reach such a goal, a survey will be applied to clients of a computer product distributor to test the hypothesis of the study in which some types of trust evolve according to the relation path, while others remain constant during all the process. The findings suggest that trust of a calculative nature, and that based on familiarity and/or identification, develop earlier and stabilize later in the relationship, whereas dispositional trust and trust in the system remain constant during the entire relationship. But the aptitude of the explanation shown by the models was relatively small, suggesting that, even though the results confirmed the hypothesis, some doubts remain about how trust is developed. Regarding the relative importance of the type of trust, we were expecting that calculated trust would be high in the beginning, and that identification-based trust would be high in mature relationships, and this was not the case. Calculated trust was the lowest of the 3 types during the entire length of the relationship, followed by identity-based trust, and we found just as much familiarity-based trust in the beginning of the relationship as at the end.